POTENCIAL DO EXTRATO DA RAIZ DA BREDEMEYERA FLORIBUNDA COMO RECURSO ERGOGÊNICO NUTRICIONAL EM RATOS SUBMETIDOS AO TREINAMENTO DE FORÇA - CLÁUDIA STELA DE ARAÚJO MEDEIROS GONZAGA (2024)
Introduction: the medicinal plant Bredemeyera floribunda Willd. is used in traditional medicine to treat snake bites, low libido, fatigue and several chronic non-communicable diseases. However, there are scarce scientific studies proving its effectiveness in increasing work activity and low libido. Hence, the objective of this study was to evaluate the effect of the aqueous extract obtained from the root bark of B. floribunda Willd. as an aid ergogenic nutritional resource on muscle strength and libido of rats subjected to resistance training. Method: An aqueous extract similar to a popular tradition was obtained from the root bark of B. floribunda. Using Wistar rats, the acute oral toxicity of the aqueous extract, the assessment of the acute and chronic aid ergogenic effect, and the libido test were performed. The product obtained was administered daily (2.33 mg/kg), three to four hours before the animals were subjected to resistance training on a vertical ladder. In the acute study, muscle strength was determined by the maximum load-carrying capacity, which was performed twice, with a two-day rest period between strength tests. The aid ergogenic effect was evaluated over 56 days, with three resistance training sessions per week. Each session consisted of at least four climbs and a 120-second rest period between them. The libido test was performed on two different days; 12 specific rats were randomly selected from the study and individually placed in contact with two female rats to determine the latency time and the number of copulations, one rat for each day. Results: The median lethal dose (LD50) was higher than the dose tested and presented loss of muscle strength, destruction and deep sleep as symptoms of toxicity. In the acute test, the intervention group presented a reduction in serum and urinary testosterone concentration, increasing the collection of the hormone in response to extraction and training. There was an ergogenic effect only in the experimental test, from the sixth week of resistance training, which was accompanied by preservation of testicular mass, providing an antioxidant effect of the compound. Regarding sexual behavior, there was no increase in libido in response to supplementation with B. floribunda. Conclusions: the extract obtained is not lethal in acute doses, however, it can affect the central nervous system. The extract is ergogenic for specific use and does not confirm the popular claim about increased libido.